MUSCLE BOOST (2024)
In the world of sports, physical effort is a constant action that leads to produce different types of muscle injuries which affect performance and the physical health of athletes, this is why during the development of the different sports practices, athletes are exposed to presenting different types of muscle injuries, either before or during sports activity (Institute National Arthritis and Musculoskeletal and Skin Diseases, 2023). In In this case, muscle tears, cramps, contractures, strains, ruptures, etc., which cause cramps, contractures, etc., which have a greater impact on the poly-articular muscles, produced by fatigue accumulation conditions, work not performed properly or unfavorable environmental conditions. For this reason, it is Early diagnosis and treatment are important to be able to intervene and ensure that the athlete returns to his activity and the recovery process as soon as possible. competition (Durán, M. Á. C, 2008).